Optimizing maize-soybean intercropping patterns under film-edge cultivation regulates soil bacterial communities to enhance productivity and water use efficiency - Hu, Jingyi; Wang, Jiaxin; Zhang, Panpan; Tian, Lixin; Yuan, Yuhao; Wei, Qian; Wang, Tao; Luo, Yan; Guo, Yaning; Wang, Xiaolin; Zhang, Xiong (Frontiers in Plant Science, 2025)
Intercropping enhances resource utilization and productivity through interspecific complementarity; however, its potential in arid-region film-edge cultivation, especially microbial-environmental interactions, remains underexplored. A two-year field experiment was conducted in film-edge cultivation in northern Shaanxi, comparing maize monoculture (CJCJ), soybean monoculture (SJSJ), and four maize–soybean intercropping patterns—2C2S, 2C4S, 4C2S, and 4C4S—to investigate how these configurations affect soil bacterial community composition and crop productivity. Results showed that the 4C2S and 2C4S patterns improved soil moisture dynamics, enzyme activities, and microbial community structure. Compared with monocropping, intercropping increased soil moisture in both crop zones, with differential regulation. In 2022, all intercropping treatments significantly increased maize rhizospheric urease, alkaline phosphatase, and sucrase activities (P < 0.05). In 2023, 2C4S significantly enhanced these three enzymes plus catalase in maize vs. CJCJ (P < 0.05), while 4C4S significantly increased soybean catalase and sucrase (2022–2023) and urease and alkaline phosphatase (2023) vs. SJSJ (P < 0.05). Intercropping improved the rhizospheric root morphology of crop. 2022 2C4S significantly increased soybean root length and average diameter at R1 stage (P < 0.05); 2023 2C4S significantly enhanced maize root dry weight, length, surface area, and volume at V12 stage vs. CJCJ (P < 0.05). Maize bacterial richness was unaffected, but 2C2S and 4C2S significantly increased soybean bacterial richness and Shannon diversity (P < 0.05). At maize V12, 2C4S and 4C4S increased Sponge phylum by 24.68% and 32.85%, and 2C4S increased Dentomonas by 22.92% vs. monocropping. At soybean R1, 2C4S increased Sponge by 7.34%, 2C4S and 4C2S increased Acidobacteria by 15.64% and 21.40%; 2C4S enriched Nitrososphaeria_A and Blastocatellia, 2C2S was dominated by Bacteroidia, and 4C4S had the highest total soybean microbiota abundance. The treatment-year interaction significantly affected maize yield and WUE (P < 0.05), and had a highly significant effect on those of soybean (P < 0.01). 2C4S significantly boosted maize yield (2022: 4.04%-33.53%; 2023: 2.58%-26.98%) and exhibited the least soybean yield reduction under intercropping compared to SJSJ. In conclusion, by regulating the soil-microbe-crop nexus, 2C4S increases maize yield, reduces soybean loss, and improves resource efficiency in arid film-edge cultivation, providing a viable strategy for intercropping in water-limited regions.